1984
DOI: 10.1016/0309-1651(84)90192-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by quercetin of the release of density dependent-inhibition of cell growth in RSV-transformed chicken cells

Abstract: The expression of src gene in dense cultures of chick embryo fibroblasts (CEF) infected by a thermosensitive mutant (NY68) of RSV released density-dependent inhibition of growth and induced in these cells a large increase in DNA, RNA and protein synthesis. This stimulation of cellular metabolism was abolished in the presence of quercetin. Furthermore, quercetin added to the culture medium also inhibited the stimulation of pp60src kinase due to the expression of transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…The identity of the ATPase responsible for steady-state glycolysis in cells that were not inhibited by either ouabain or rutamycin remained undetermined. Similar conclusions were reached by Jullien et al (8) based on studies of ATP turnover with Rous sarcoma virus-transformed cells. They also observed that quercetin inhibited ATP turnover.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…The identity of the ATPase responsible for steady-state glycolysis in cells that were not inhibited by either ouabain or rutamycin remained undetermined. Similar conclusions were reached by Jullien et al (8) based on studies of ATP turnover with Rous sarcoma virus-transformed cells. They also observed that quercetin inhibited ATP turnover.…”
supporting
confidence: 72%
“…A few were sensitive to oligomycin, suggesting that the mitochondrial ATPase may be activated. Other cell lines were insensitive to both ouabain and oligomycin, but most cell lines were highly sensitive to the bioflavonoid quercetin (7,8). In many cell lines glycolysis was actually stimulated by oligomycin, as would be expected of cells with highly active mitochondria that compete for ADP and Pi required for glycolysis.…”
mentioning
confidence: 96%
“…Quercetin has been shown to inhibit DNA, RNA, and protein synthesis in NY68-infected chick embryo fibroblast (Jullien et al, 1984), 12-O-tetradecanyl-13 phorbol acetate-induced ODC activity in mouse skin. This suggests that Emblica officinalis methanolic fruit extract potentially inhibits polyamine biosynthesis and consequently the rate of DNA synthesis at both the doses.…”
Section: Discussionmentioning
confidence: 99%
“…По-видимому, ýто в значительной степени обусловлено ингибирующим влиянием данных полифенолов на цепь биохимических событий, связанных с клеточным ростом [9]. Так, еще в ранних исследованиях было показано, что кверцетин подавлял аýробный гликолиз в опухолевых клетках, а также ингибировал белковый синтез в клеточных культурах ряда опухолей и повышал в ýтих клетках уровень циклического аденозинмонофосфата (АМФ) [1,41,42]. В ýтом контексте отметим роль активируемой 5΄АМФ протеинкиназы АМФК (AMPK), контролирующей ýнергетический баланс клетки.…”
Section: Conflict Of Interestunclassified